A load-storage integrated control strategy to improve power regulation performance in a microgrid. (October 2017) - Dou, Xiaobo; Sun, Shuai; Zhao, Bo; Yin, Jiawei; Wu, Zaijun; Gu, Wei; Hu, Minqiang; Cao, Shuijin
Highlights: The adjustable power range is expanded by the flexible load-storage integrated control strategy. The ability to participate in the demand response of a microgrid is improved. Multi-objective optimization can be realized in different operation states of a microgrid. The mirror droop control strategy can effectively promote the voltage to reinforce the stability of a microgrid. Abstract: To introduce flexible power regulation into a microgrid, this paper proposes a load-storage integrated control strategy (ICS), consisting of an economic control model (CCM) and an efficient control model (FCM). CCM is adopted to reduce the action cost of controllable loads (CLs) and the operation cost of energy storage and to improve the efficiency of a microgrid when it operates in a grid-connected state. FCM is adopted to achieve rapid, accurate power regulation to improve the stability of a microgrid when it operates in an islanded state. FCM not only can maintain the voltage and frequency of the system alone, but it also can share the regulated power with other distributed generators (DGs) under the proposed mirror droop control strategy. Additionally, a customer satisfaction model (CSM) is introduced to help customers select the control models and parameters of ICS in order to meet different requirements for various customers. A physical prototype, load-storage integrated control unit (ICU), is designed to implement ICS. Both numerical simulations and experimental tests successfully verify that ICS or ICU can provide more economic and more efficient power regulation in contrast to respectively regulating controllable loads and energy storage.